Ferns in fragment of Atlantic forest, Sapé, Paraíba, Brazil - Silvestre, Leandro Costa; Xavier, Sergio Romero da Silva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
This study presents a floristic-taxonomic survey of species of ferns that occur in the Private Reserve of Pacatuba Farm in the city of Sapé, in the state of Paraíba, Brazil. The protected area is a semideciduous seasonal forest with a total area of 266.53 hectares. We registered ten families, 18 genera and 24 species of ferns. The most representative families were Pteridaceae with eight species and Thelypteridaceae with four species. The species Adiantum obliquum Willd., Adiantum petiolatum Desv., Didymoglossum ovale E. Fourn. and Thelypteris macrophylla (Kunze) C.V. Morton are cited as new registers for the state of Paraíba. The registration of these new occurrences for the state is an indication of the need for research focused on the flora of seedless vascular plants to better understand the biodiversity of the state of Paraíba.
Keywords: New records; Northeast Brazil; Taxonomy; Floristics; Seedless Plants